Potret Prospek Pendidikan Agama Islam Kekinian: Integrasi Inklusivitas Islam dalam PAI - Hunaida, Wiwin Luqna (Didaktika Religia, 2016)
The discourse of Islamic education in the era has become daily topics menu ofIslamic thinkers and educatorors. The question deals with the problem onwhether Islamic education has prospects this time, or if Islamic education willgo bankruptcy. Noting the spiritual thirst of modern society, poor guidance, andtheir need to get solution to the various problems of everyday life, the role ofIslamic education is vital. Religion and education are two things that are relatedand complementary. Religion in national education systems essentially becomespart of the curriculum, because religion is intended to develop true Indonesians,"Indonesians who are faithful and devoted to God Almighty". In addition, themost fundamental of Islamic eeducation in schools is the expectation of producinghuman beings who really understand religion as well as to implement in lifeindicated partly by promoting peace, tolerance, fairness and honesty